Adherence to the use of personal protective equipment by the nursing staff in the hospital environment (Research, Society and Development, 2020)
Objective: To analyze the adherence of the nursing staff to the use of personal protective equipment. Specifically, the objective was to describe occupational accidents that may occur when I do not use Personal Safety Equipment (PPE), to verify the existence of a qualification and training program to raise awareness and better working conditions for the professional, and to evaluate the knowledge of the workers. professionals to use Personal Protective Equipment. Methodology: This is an observational, descriptive and exploratory field study with a quantitative approach to the data, performed at the Gentil Filho General Hospital, in the city of Caxias, Maranhão. Results: The professionals perform the washing before and after each procedure performed in the sector. All research participants (100%) stated that they use procedure gloves, mask, overcoat and remove gloves immediately after contact with the patient. Regarding the use of aprons in procedures with splashes containing biological materials, some participants reported not using them, however, the minimum percentage was 20%. About 20% of survey participants do not use PPE to prepare medication. Conclusion: The use of equipment to prevent health problems of nursing professionals is important, since they are exposed to the imminent risk of contamination in the service sector.